2020
DOI: 10.1021/acsbiomaterials.0c00804
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials as Smart Immunomodulator Delivery System for Enhanced Cancer Therapy

Abstract: Immunomodulatory therapeutics, which is conducive to overcoming tumor tolerance and restoring normal immune responses, has been proposed as a promising approach for enhanced cancer therapy and clinical advancement. However, issues including cytokine syndrome, inefficient delivery, hepatic dysfunction, and severe adverse reactions remain to be resolved. It is particularly critical to develop delivery technologies to overcome these limitations and further improve antitumor efficacy. With the continuous developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 187 publications
0
28
0
Order By: Relevance
“…This overview will focus on biomaterials that provide sustained release in vivo for vaccines against infectious disease. Several reviews focus more specifically on cancer (Abdou et al, 2020;Yan et al, 2020;Yuan, Liu, Wang, Sun, & Chen, 2020;Zhang, Billingsley, & Mitchell, 2018;Y. Zhao, Guo, & Tang, 2018b), which we will not discuss.…”
Section: The Interplay Between the Realities Of The Immune System And Vaccine Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…This overview will focus on biomaterials that provide sustained release in vivo for vaccines against infectious disease. Several reviews focus more specifically on cancer (Abdou et al, 2020;Yan et al, 2020;Yuan, Liu, Wang, Sun, & Chen, 2020;Zhang, Billingsley, & Mitchell, 2018;Y. Zhao, Guo, & Tang, 2018b), which we will not discuss.…”
Section: The Interplay Between the Realities Of The Immune System And Vaccine Technologymentioning
confidence: 99%
“…This overview will focus on biomaterials that provide sustained release in vivo for vaccines against infectious disease. Several reviews focus more specifically on cancer (Abdou et al, 2020; J. Li et al, 2020; Yan et al, 2020; Yuan, Liu, Wang, Sun, & Chen, 2020; Zhang, Billingsley, & Mitchell, 2018; Y. Zhao, Guo, & Tang, 2018b), which we will not discuss. Several excellent reviews are available that go into depth on particular types of biomaterials, and we have made an effort to direct readers to reviews as appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Even when cell entry is permitted, synthetic chemicals normally have a small volume, and therefore a short retention period in the body after their uptake 9 . These small chemicals have recently been embedded in polymers, 10 liposomes, 2 or nanoparticles 11 to increase the efficiency of their transportation and to improve their retention times 12 . Discotic materials with planar and nanoparticle functions 13,14 are potential carriers of these chemicals and should increase their bioavailability; therefore, we investigated their toxicity based on their inhibition of Escherichia coli growth as well as a simple proteomic analysis.…”
Section: Figurementioning
confidence: 99%
“…Recent reviews [ 41–43 ] have extensively discussed the ability of nanomaterials to have an impact on cancer immunotherapy; however, these reviews do not focus specifically on the impact of multifunctional platforms that have shown to be effective in enhancing interactions with immune cells and improving cancer therapy response. Although cytokines and antigens for therapeutic delivery are biological materials and have been extensively reviewed, [ 44–46 ] this review will talk about the novelty of engineered biological materials such as multispecific and multifunctional antibodies.…”
Section: Introductionmentioning
confidence: 99%